Identification of TOD Intersection Through Study of Architectural Place Attachment in Lhokseumawe City - Deni Deni; Hendra A.; Aris Munandar (Universitas Bandar Lampung (UBL), 2026)
Public transportation services in Lhokseumawe City are not available, requiring people to have private transportation, the number of which continues to increase, which can complicate the mobility of city residents. Therefore, an integrated public transportation study approach is needed by identifying TOD meeting points through a study of architectural spatial attachment in the city. The study uses a mixed method, qualitative to obtain data on the ideal achievement of transportation center points, and quantitative to obtain an emotional impression of space. The object of purposive research is only focused on the protocol roads of Lhokseumawe City. Research data becomes units of analysis through the idea of TOD urban space that connects residential areas with the center of community mobility. Meanwhile, the idea of place attachment in architecture is used as an analytical thinking tool to find the emotional relationship of the community to the place as the forerunner to the discovery of TOD meeting points. The results of the analysis explain that zone 2 has better spatial quality and quantity compared to other zones based on a study of functional and emotional architectural place attachment.